Effects of 12 Weeks Concentric and Eccentric Resistance Training on Neuromuscular Adaptation of Quadriceps Muscle - Talieh Bagheri; Bahram Abedi; Nosratollah Hedayatpour (Shiraz University of Medical Sciences, 2020)
Manipulating resistance training program variables is a commonly used tool for optimizing maximum muscle strength in rehabilitation and/or exercise training programs. The current study purposed to compare the effects of 12 weeks of concentric and eccentric resistance training on neuromuscular adaptation of quadriceps muscle. Methods  Twenty-six male subjects (age, mean ± SD, 22.1 ± 2.4 yr; body mass, 72.3 ± 9.9 kg; height, 1.75 ± 0.08 m) were recruited for this controlled laboratory study. Subjects were randomly divided into two groups: the eccentric training group (No = 13) and the concentric training group (No = 13). The maximal isometric voluntary contraction (MVIC) of quadriceps muscles, vertical jumping, and surface electromyography (EMG) signals were recorded before and after 12 weeks of resistance concentric and eccentric training. Repeated-measures Analysis of Variance (ANOVA) was used to test differences between means before and after resistance training. Results  The maximal isometric voluntary contraction of the quadriceps muscle and vertical jumping were significantly increased after eccentric and concentric training (p <0.05). Eccentric exercise resulted in a greater increase in maximal isometric voluntary contraction of the quadriceps muscle and vertical jumping compared to concentric training (p <0.05). The amplitude of surface EMG signals was also significantly increased after eccentric and concentric training (p <0.05), with a greater increase observed in the eccentric than the concentric training group (p <0.05). Conclusion  The results of this study showed higher increases in muscle force output and EMG activity after eccentric training. This may indicate that stretch combined with overloading is the most effective stimulus for enhancing neuromuscular activity during dynamic resistance exercise. The knowledge gained from this study may be relevant for designing exercise and/or rehabilitation training to improve muscle output.